Communication and sport surveying the field - Billings, Andrew C.; Butterworth, Michael L.; Turman, Paul D. (Los Angeles SAGE, 2018)
This book examines a wide array of topics necessary to understand sports media, rhetoric, culture, and organizations from micro- to macro-level issues.
Includes bibliographical references (pages 304-339) and index.
Keywords: Mass media and sports